Influence Factor Analysis Students’ Learning Outcomes in the Course of Defense and Security Education to Promote Creativity and Problem-Solving Ability: Case Study at VNU, Hanoi - Trong Lap, Nguyen; Son, Nguyen Hoanh; Thanh, Nguyen Chi (VNU Journal of Science: Education Research; Vol 39 No 1S, 2023)
Using factor analysis, the research shows that there are five factors affecting students’ learning outcomes in the course of Defense and Security Education with the view to promoting students’ creativity and problem-solving ability. The factors include i) Students’ learning awareness; ii) Their learning methods; iii) The teaching and learning methodology; iv) The course content; and v) Learning materials. The findings derived from the linear regression analysis reveal that the instructional methodology employed (with a coefficient of 0.4820) and students' academic diligence (with a coefficient of 0.284) exert the most substantial influence on students' scholastic outcomes. Subsequently, the subsequent factors, ranked in descending order of impact, encompass: the instructional content (with a coefficient of 0.27), pedagogical resources (with a coefficient of 0.203), and students' learning approaches (with a coefficient of 0.114). Employing Exploratory Factor Analysis (EFA) facilitates the determination of: The levels of impacts of these factors on the students’ learning outcomes in the course oriented towards creativity and problem-solving ability promotion are varied. To be more specific, the teaching and learning methodology has the strongest influence and is the decisive factor in the students’ learning outcomes. The one with the least impact is the students’ learning methods. Based on these findings, it is necessary that Vietnam National University, Hanoi offer the Defense and Security Education course with renovated teaching and learning methodology towards students’ creativity and problem-solving ability promotion, provoke their proactiveness, positivity and creativity in learning, and focus on increasing their learning awareness to improve the students’ learning outcomes in this course. The results of the experimentation demonstrate that the organization of teaching and learning activities within the subject "National Defense and Security Affairs", oriented towards enhancing problem-solving capabilities and fostering creativity, yields numerous positive variations in students' academic achievements (following the five-step approach). Consequently, further studies are warranted to continue investigating this matter.